Tracing Neurological Diseases in the Presymptomatic Phase: Insights From Neurofilament Light Chain - Gaetani, Lorenzo; Parnetti, Lucilla; Calabresi, Paolo; Di Filippo, Massimiliano (Frontiers in Neuroscience, 2021)
The identification of neurological diseases in their presymptomatic phase is a fundamental goal to be aimed at in the coming years. This step is necessary both to optimize early diagnostics and to verify the real effectiveness of experimental disease modifying drugs in the early stages of the diseases. Among biomarkers able to detect neurological diseases already in their preclinical phase, neurofilament light chain (NfL) has given the most promising results. Recently, its measurement in serum has allowed to identify neurodegeneration in diseases such as multiple sclerosis and Alzheimer's disease up to 6-10 years before the onset of symptoms. Similar results have been obtained in conditions such as frontotemporal dementia and amyotrophic lateral sclerosis, up to 2 years before clinical onset. The study of the longitudinal dynamics of serum NfL also revealed interesting aspects on the pathophysiology of these diseases in the preclinical phase. Here, we sought to discuss these very recent findings on serum NfL in the presymptomatic phase of neurological diseases.